PERSEPSI MASYARAKAT TERHADAP KEBERADAAN HUTAN KEMASYARAKATAN DI DESA MERAGUN KECAMATAN NANGA TAMAN KABUPATEN SEKADAU - Heryatna, Dhani; Zainal, Sofyan; Husni, Harnani (Universitas Tanjungpura, 2016)
Community forests in the Meragun village is the designed of Indonesian Forestry Ministry which has the goal to improve the welfare of society. Relationship between community and existence of community forests has led to the perception the public as an attempt to maintain and preserve forests. The purpose of this study was to determine the public perception of the existence of a community forest in the Meragun village, Sekadau district and factors that influence. The method based on survey and sampling techniques or interviews the respondents conducted by purposive sampling. The number of respondents were 81 respondents. The results showed the level of public perception to the existence of a community forest in the Meragun village tend to be higher as many as 50 respondents (61.72%) have a high perception of the existence of a community forest in the Meragun village, 23 respondents (28.39%) perceive moderate and 8 (9.87%) respondents who had a low perception. Keywords : Community forests, Public perception